Strategi Pembentukan Sikap Wajib Pajak Dalam Mewujudkan Program Electronic Filing (E-Filing) Di Kota Pontianak Dengan Pemahaman Menuju Era Ekonomi Digital - Sri Haryaningsih; Antonia Sasap Abao (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aims to determine what factors shape taxpayer attitudes in realizing the Electronic Filing (E-Filing) program. The characteristics of taxpayers that are reflected by cultural, social and economic conditions will dominate the behavior of taxpayers which is reflected in their level of awareness in paying taxes. The Compliance Attitude in implementing the Electronic Filing (E-Filing) program is certainly not formed by itself, but is formed by a process, in forming compliance, it must be preceded by the awareness of the taxpayer. There are several factors that influence people's attitudes in paying taxes are still low, namely: a. cultural and historical causes; b. lack of information from the government to the people c. Individual atmosphere (unable to operate the internet, lazy, no direct reward. Tax awareness is the willingness to fulfill its obligations, including being willing to contribute funds to the implementation of government functions by paying tax obligations. This obligation is carried out without any element of coercion from any party. those who have high awareness will carry out their tax obligations in accordance with the applicable tax regulations. That way the Self Assessment System can be implemented properly. In other words, the higher the level of taxpayer awareness, the higher the level of taxpayer compliance in paying. in the optimization of taxpayers to switch to using e-filing by enhancing the image of Good Governance which can lead to mutual trust between the government and the taxpayer community, so that tax payment activities will become a necessity and a willingness, not a obligation. Thus a pattern of relations between the state and society is created in fulfilling rights and obligations that are based on mutual trust. For the sake of realizing the Digital Economy in Indonesia